Design As Research: Positions, Arguments, Perspectives - Joost, Gesche; Bredies, Katharina; Christensen, Michelle; Conradi, Florian; Unteidig, Andreas (Board of International Research in Design, 2016)
Are there differences between design practice and the practice of design research? What alliances between text and artefact are possible in the search for new knowledge? How does design research translate and transform theories and methods from other disciplines? Is design research moving towards becoming a formal discipline and, if so, would this really be an advantage? 16 international authors address these four different aspects in the form of personal statements, and 19 researchers share their reflections based on their experience of having carried out a practice-based PhD. This book investigates the status quo of things in the multi-faceted and constantly evolving field of design research, and outlines the elementary issues faced by researchers. The compendium is a survey of a fast-growing field and, at the same time, provides pointers for personal orientation. With statements from: Uta Brandes, Rachel Cooper, Clive Dilnot, Michael Erlhoff, Alain Findeli, Bill Gaver, Ranulph Glanville, Matthias Held, Wolfgang Jonas, Klaus Krippendorff, Claudia Mareis, Mike Press, Elizabeth B.-N. Sanders, Arne Scheuermann, Cameron Tonkinwise, Brigitte Wolf Gibt es Differenzen zwischen Designpraxis und Designforschungspraxis? Welche Allianzen zwischen Text und Artefakt sind auf der Suche nach neuem Wissen möglich? Wie werden Theorien und Methoden aus anderen Disziplinen durch die Designforschung übersetzt und transformiert? Begibt sich die Designforschung auf den Weg zu einer formalen Disziplin, und wäre dies überhaupt ein Gewinn? 16 internationale Autor/innen widmen sich in persönlichen Stellungnahmen diesen vier Aspekten, und 19 Forscher/innen schildern Betrachtungen, basierend auf Erfahrungen, die sie durch das Absolvieren ihres praxisbasierten PhD sammeln konnten. Dieses Buch fragt nach dem aktuellen Stand der Dinge in dem vielfältigen und im ständigen Wandel begriffenen Feld der Designforschung und skizziert die Grundfragen der forschenden Praxis. Das Kompendium ist die Bestandsaufnahme eines schnell wachsenden Bereiches und zugleich ein Kompass zur persönlichen Orientierung. Mit Stellungnahmen von: Uta Brandes, Rachel Cooper, Clive Dilnot, Michael Erlhoff, Alain Findeli, Bill Gaver, Ranulph Glanville, Matthias Held, Wolfgang Jonas, Klaus Krippendorff, Claudia Mareis, Mike Press, Elizabeth B.-N. Sanders, Arne Scheuermann, Cameron Tonkinwise, Brigitte Wolf